Impact of myasthenia gravis on family planning: How do women with myasthenia gravis decide and why?. Issue 3 (18th June 2015) - Ohlraun, Stephanie; Hoffmann, Sarah; Klehmet, Juliane; Kohler, Siegfried; Grittner, Ulrike; Schneider, Alice; Heuschmann, Peter U.; Meisel, Andreas
ABSTRACT Introduction: We analyzed the impact of myasthenia gravis (MG) on decision‐making in family planning by women with the disease. Methods: In a cross‐sectional, anonymous survey, a standardized questionnaire was sent or handed out to 1, 637 women with MG. Results: In total, 801 questionnaires were eligible for analysis. Over fifty percent of the patients had abstained from having children due to MG. The concern mentioned most often was the possible influence of MG medication on the unborn child (87.1%). Spouses/partners (91.8%) and MG treating physicians (82.9%) were the most important persons involved in the decision‐making process. Higher age and personal experience of intensive‐care treatment for MG were independently associated with the decision to abstain from having children. Lower level of knowledge was independently associated with the probability of discouraging other MG patients from having children. Conclusions: Women with MG need specific guidance about family planning issues, which may lead to lower rates of voluntary childlessness. On the basis of our data, more specific hypotheses can be generated that require prospective investigation. Muscle Nerve 52:371–379, 2015